Islamic Science and Some Physico-Philosophical Thoughts From a Mathematical Physics Point of View - Zainal Abdul Aziz (Universiti Sains Islam Malaysia, 2024)
This article attempts to discuss on some thoughts relating to the working philosophy (skimming through mainly its research methodology) o f a Muslim mathematical physicist. We believe that this undertaking in turn would eventually stimulate and enhance oneself methodically with excellent research skills and capabilities. Moreover we think that by upholding to this viewpoint, one would be able to sustain consistently these outstanding competences. In order to achieve this optimal goal, a desire,for the ambiance o f an Islamic Science is shown to be unavoidable.